How to get a great job : a library how-to handbook (Skyhorse Pub., 2011)
In our difficult time, or at any time, knowing how to find a great job is a necessary skill. All the resources you need for a successful job search are at your fingertips-and completely free-at your public library. It can be a daunting task, so here is expert advice on how to conduct proper research, build networksof friends and colleagues, put together a great resume, research industries that are constantly changing, prepare for an interview, negotiate a contract or a salary, and more.